Banking policy compatibility with aaiofi investment standard federation: Sudanese banking study of 2010-2020 (Entrepreneurship Journal for Finance and Business, 2022)
The problem of research is responsible for the question: How important is the policies of Sudanese banks with the Forensic Reviews of Investment and Auditing of Islamic Financial Institutions from 2010-2020? The aim of this research is also aimed at identifying the following: The concept of monetary policy in Islamic banks accounting for Islamic financial institutions and the criterion of the forensic posts issued by the extent to which bank policies agreed with the Forensic Reviews of Accounting and Auditing of Islamic Financial Institutions "Study of Sudanese banks from 2010 2020. The search assumes that the policy policies are consistent with the criterion of the Shari'a for investment by the Accounting and Review of Islamic Financial Institutions. Projects funded in formulas with legitimate anti-investment standards. The bank's policy in the acquisition of clients is experienced in the management of projects financed in the formula of participation with the legitimate IPO standards and the Bank's policy is consistent to adopt the concept of business leadership through participation formats with legitimate ipments.